Analisis Penentuan Strategi Digital Marketing pada Toko Tumblrin - Maudina Inayah; Eko Cahyo Mayndarto; Orni Juliati (Global Leadership Organizational Research in Management, 2024)
The emergence of digitalization in marketing presents opportunities and changes to large, medium and small business actors. Implementing digitalization in marketing accompanied by creating and determining digital strategies marketing. A digital marketing strategy is a marketing plan or activity who use digital media, such as the internet or online marketing, to achieve marketing goals and expand consumer reach. Strategy digital marketing is the right choice for SMEs/MSMEs, incl TumblrIn, marketing products and carrying out promotions. Research purposes This is to find out how to determine a digital marketing strategy, implementation and results of the impact of determining a digital marketing strategy on TumblrIn Store. In this research, quantitative and qualitative descriptive methods were used used to provide a deeper picture and understanding comprehensive approach to the phenomenon under study. Additionally, for collection data, the researcher used observation and documentation techniques from the final assignment project which is the final assignment for graduation after taking part Merdeka Campus Certified Independent Study program at PT. Nurul Fikri Create Innovation. The research results show that digital strategy marketing on TumblrIn has been determined using SWOT Analysis (Strengths, Weaknesses, Opportunities, Threats), STP (Segmentation, Targeting, Positioning), and Marketing mix. Implementation of digital marketing strategies in TumblrIn has been doing quite well and achieved several goals. Utilization online media in digital marketing strategies has also been successful quite a lot of traffic, although not all online media get the same amount of traffic. However, the amount of traffic has exceeded initial targets can be converted into potential customers.).